Mhd free convection flow near a moving vertical plate in the presence of thermal radiation: an analytical solution - Das, Kalidas (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
An exact solution of the problem of the unsteady free convection flow of a viscous elec-